Salvianolic acid A regulates pyroptosis of endothelial cells via directly targeting PKM2 and ameliorates diabetic atherosclerosis - Zhu, Ji; Chen, Hang; Le, Yifei; Guo, Jianan; Liu, Zhijun; Dou, Xiaobing; Lu, Dezhao (Frontiers in Pharmacology, 2022)
Abstract Rescuing endothelial cells from pyroptotic cell death emerges as a potential therapeutic strategy to combat diabetic atherosclerosis. Salvianolic acid A (SAA) is a major water-soluble phenolic acid in the Salvia miltiorrhiza Bunge, which has been used in traditional Chinese medicines (TCM) and health food products for a long time. This study investigated whether SAA-regulated pyruvate kinase M2 (PKM2) functions to protect endothelial cells. In streptozotocin (STZ)-induced diabetic ApoE-/- mice subjected to a Western diet, SAA attenuated atherosclerotic plaque formation and inhibited pathological changes in the aorta. In addition, SAA significantly prevented NLRP3 inflammasome activation and pyroptosis of endothelial cells in the diabetic atherosclerotic aortic sinus or those exposed to high glucose. Mechanistically, PKM2 was verified to be the main target of SAA. We further revealed that SAA directly interacts with PKM2 at its activator pocket, inhibits phosphorylation of Y105, and hinders the nuclear translocation of PKM2. Also, SAA consistently decreased high glucose-induced overproduction of lactate and partially lactate-dependent phosphorylation of PKR (a regulator of the NLRP3 inflammasome). Further assay on Phenylalanine (PKM2 activity inhibitor) proved that SAA exhibits the function in high glucose-induced pyroptosis of endothelial cells dependently on PKM2 regulation. Furthermore, an assay on c16 (inhibitor of PKR activity) with co-phenylalanine demonstrated that the regulation of the phosphorylated PKR partially drives PKM2-dependent SAA modulation of cell pyroptosis. Therefore, this article reports on the novel function of SAA in the pyroptosis of endothelial cells and diabetic atherosclerosis, which provides important insights into immunometabolism reprogramming that is important for diabetic cardiovascular disease complications therapy.